Measures to tame credit growth: Are they effective? - Adam Geršl; Martina Jašová (Charles University in Prague, Institute of Economic Studies (IES), 2012)
This paper focuses on policy measures taken to curb the private sector credit growth in the period 2003-2008. Our analysis is based on an original survey performed on eleven central banks in Central and Eastern Europe (CEE). The findings reveal high intensity of policy intervention: altogether 82 measures were taken in CEE in the period. This paper combines direct assessment of particular central authorities and a difference-in-differences method to find out whether the measures applied were effective in slowing down the credit growth. Deriving from country experiences, the paper argues that in order to eliminate adverse impacts, policy measures should include combination of monetary and prudential tools with special emphasis on domestic environment and role of foreign banks in the CEE region.
Keywords: E44; E51; E52; E58; G21; 330; credit growth; monetary policy; macroprudential policy; Central and Eastern Europe